PEMBUATAN DAN KARAKTERISASI MEMBRAN ELEKTRODA SELEKTIF ION Cu(II) MENGGUNAKAN IONOFOR Na2S SEBAGAI SENSOR KIMIA - Rosyada, Amrina; Arif, Moh. Syaiful; Panggabean, Aman Sentosa (JURNAL ATOMIK, 2025)
Preparation and characterization of Cu(II) ion selective electrode membranes based on polyvinyl chloride (PVC) using sodium sulfide (Na2S) as the ionophore has been done. The use of PVC polymer functions as a material that strengthens the properties of the membrane mixed with Na2S to form a homogeneous membrane and can reduce the risk of leaks in the membrane used. However, PVC has stiff properties, so a plasticizer in the form of DOP was needed to reduce intermolecular forces and make the membrane elastic. The preparation was carried out with the composition Na2S : PVC : DOP, namely 6 : 3 : 1. The membrane was doped with CuSO4 solution for 7 days and the Cu2+ ESI performance was measured to increase the optimal conductivity of the membrane, it is done by doping the membrane, namely by inserting 1 M Cu2+ dopant metal. The ESI Cu2+ performance results show a solution composition of 1:2 CuSO4:KNO3 and works well in the composition range 10-5 - 10-1 M, with a Nernst factor value of 28.9 mV/decade and a detection limit of 1.01×10-5 M. The response time of ESI Cu2+ was 10-60 seconds and can be used for 3 days. ESI Cu2+ works in the pH range 4-6 and the presence of interfering ions Cd2+, Zn2+, Cl-, NO3- and SO42- does not affect the performance of ESI Cu2+.